Trending and advocating mobile food truck business: a Malaysian consumer perspective - Boon Chui Teo, Carol; Amanina Binti Othman, Nurul; Binti Izzudin, Izznie; Nabeela Binti Omar, Nur; Husna Binti Zaidi, Zaizatul (International Journal of Engineering and Technology, 2018)
Mobile food truck business has been around for years in the Western countries. However, in Malaysia, it is considered at introductory stage and there are more than 100 varieties of this new mobile food truck concept that is trending today and it is growing rapidly in popularity. Since this concept is relatively new in Malaysia, it is without problems and challenges including difficulty in getting operating license and permit from local authorities, finding strategic locations to park trucks as well as relatively unknown consumer perception towards such unorganized food sector. Hence this study aims to examine consumer perspective in terms of perception, attitude and acceptance towards mobile food truck that seems to be expanding with the aid of social media and as a good small business investment. It appears there is increasing willingness to pay (WTP) for food from mobile food trucks but there is dearth of studies in this area. Methodology utilised data collected through personal interviews with food truck owners and local authority. Subsequently a survey was administered to 200 food truck customers. Findings indicate significant results on perception, attitude and acceptance towards WTP for mobile food. Some recommendations in advocating this new business concept are discussed.Â Â